1991
DOI: 10.1002/lsm.1900110607
|View full text |Cite
|
Sign up to set email alerts
|

In vivo canine coronary artery laser irradiation: Photodynamic therapy using dihematoporphyrin ether and 632 nm laser. A safety and dose‐response relationship study

Abstract: This study examined the safety and dose-response relationships of 632-nm laser irradiation of photosensitized normal coronary arteries in 27 dogs. Fifteen received 2.5 mg/kg dihematoporphyrin ether (DHE), seven received no sensitizer, and five had coronary instrumentation but no laser (sham laser procedures) at nine coronary sites--four sensitized, five non-sensitized. Laser energy of 82 to 1,640 J/cm2 was delivered via a 584 microns diffusing-tip optical fiber, providing estimated tissue fluences of 20 to 410… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In experimental treatments of canine coronary arteries in vivo, light doses Ͼ200 J/cm 2 elicited angiographic spasm, histological necrosis, and even transmural injury. 18 In this study, the cases of premature death were ascribed to the effects of coronary artery spasm, because only minor medial damage was seen in some of these specimens. In fact, even at high light doses, no embolization, vessel perforation, or aneurysmal dilatation was seen.…”
Section: Rockson Et Al Photodynamic Therapy In Cardiovascular Medicinementioning
confidence: 85%
See 1 more Smart Citation
“…In experimental treatments of canine coronary arteries in vivo, light doses Ͼ200 J/cm 2 elicited angiographic spasm, histological necrosis, and even transmural injury. 18 In this study, the cases of premature death were ascribed to the effects of coronary artery spasm, because only minor medial damage was seen in some of these specimens. In fact, even at high light doses, no embolization, vessel perforation, or aneurysmal dilatation was seen.…”
Section: Rockson Et Al Photodynamic Therapy In Cardiovascular Medicinementioning
confidence: 85%
“…The light is then delivered to the treatment site either directly or via hollow wave guides or fibers terminating in optical configurations to achieve either a circumferential, segmental, or conical beam profile. 16 Radially emitting fibers, with a variety of designs, have been used for endovascular PDT in animals, [17][18][19] and in one case, a 2-patient clinical study. 17 Another important advance in photoangioplasty is the development of compact, portable, and relatively inexpensive diode-based lasers to replace the older, large systems requiring special electrical and plumbing infrastructures; the latter are mostly dye lasers pumped by another laser (argon, 19 -21 KTP YAG) or pulse lasers (copper vapor).…”
Section: Mechanism Of Pdt Actionmentioning
confidence: 99%
“…In 1991, Mackie et al [20] reported that a light dose, greater than or equal to 200 J/cm 2 , elicited angiographic spasms, histological necrosis, and transmural injuries to canine coronary arteries. In this study, no adverse events concerning laser irradiation were detected in any patients.…”
Section: Pdt Studiesmentioning
confidence: 99%
“…There have been few reports on the efficacy of PDT in the treatment of atheroma, [11][12][13][14][15][16][17][18][19][20][21][22][23] and we were unable to find any reports using the YAG-OPO laser. In this present study we conducted PDT using the YAG-OPO laser in an intravascular approach on atherosclerotic rabbit aortas, investigating the regression effect on hypertrophic intima.…”
mentioning
confidence: 99%